Evidence of a Novel Gene from Aeromonas hydrophila Encoding a Putative Siderophore Receptor Involved in Bacterial Growth and Survival - Shaw-Wei D. Tsen (AboutScience Srl, 2008)
The pathogenic bacterium Aeromonas hydrophila has been shown to exclusively utilize a ligand exchange mechanism for siderophore-mediated iron uptake, with a single nonspecific siderophore receptor facilitating iron exchange. However, the genes involved in this process, including the gene encoding the nonspecific receptor, are unknown. Here we identify and characterize a novel gene, nsr1, from A. hydrophila that encodes a putative protein with high homology and significant predicted structural similarities to the FhuA protein and other known ferric-siderophore receptors. This protein appears to localize on the cell membrane and is likely to be the receptor involved in the ligand exchange siderophore-mediated iron uptake mechanism of A. hydrophila. It is expected that this information may lead to the development of new antibiotics targeting either nsr1 or its gene product for use in controlling A. hydrophila infection.